Influence of Anisotropy Induced by Microcracks on Effectiye Elastic Properties - Gambin, B.; Gałka, A.; Telega, J. J.; Tokarzewski, S. (Engineering Transactions, 2005)
The influence of microcracks distribution on macroscopic elastic properties of composites with a specific structure is studied. The model predicts the properties of laminates made of materials in which fracture process leads to appearance of many microcracks distributed practically uniformly. The method of solution is based on the so-called reiterated homogenization with two different scales of inhomogeneities. The smaller scale is connected with microcracks size. After homogenization performed with the help of FEM an anisotropic homogeneous elastic material is obtained. The anisotropy is implied by directional distribution of microcracks. On the second larger scale, random mixture of two or more different anisotropic elastic materials is considered.